HLA-D subregion expression by thyroid epithelium in autoimmune thyroid diseases and induced in vitro. - Todd, I; Pujol-Borrell, R; Abdul-Karim, B; Hammond, L; Feldmann, M; Bottazzo, G (1987)
Human thyroid epithelial cells (thyrocytes) express HLA Class II molecules in autoimmune thyroid diseases (ATD). Normal thyrocytes do not express Class II, but can be induced to do so by culture with interferon-gamma (gamma-IFN). We have examined HLA-D subregion expression in sections and monolayers of thyroid by indirect immunofluorescence using appropriate monoclonal antibodies. The results indicate that, in ATD, the incidence and intensity of Class II subregion expression by thyrocytes varies between patients, and follows the pattern DR greater than DP greater than DQ. The same hierarchy is observed in cultured normal thyrocytes treated with gamma-IFN: strong induction of Class II, and of DP and DQ in particular, requires relatively high concentrations of gamma-IFN or additional factors such as thyroid stimulating hormone. These findings suggest that HLA-D subregion expression by thyrocytes in on-going ATD is determined by the levels of disease related factors in the affected tissue.